DIAMOND-BEARING COHS FLUIDS IN THE MANTLE BENEATH HAWAII - Frezzotti M.L.; Peccerillo A. (My University, 2007)
We apply Raman microspectroscopy to exceptionally high-density CO2 (+ H2O + H2S) fluid inclusions containing nanocrystalline diamonds, which are present in garnet pyroxenites from Salt Lake Crater from Oahu (Hawaii), and show for the first time the presence of free diamond-bearing carbonate-rich fluids/melts, originated within the asthenospheric mantle at depths greater than 150 km, in the diamond stability field. We argue that these fluids can migrate, generate compositional and rheological modifications to form small-scale fluid-rich regions beneath Hawaii, which are easily melted to give enriched basaltic magmas at normal mantle temperatures. © 2007 Elsevier B.V. All rights reserved.
Keywords: CARBONATE-RICH MELT; CO2; DIAMOND; FLUID INCLUSIONS; HAWAII; PYROXENITE; WATER